2014
DOI: 10.1007/s10549-014-2885-y
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of the incidence of late effects in 5-year survivors of breast cancer

Abstract: Purpose Late effects of breast cancer affect the quality of survivorship. Using administrative data, we compared the occurrence of almost all ICD9 codes among older breast cancer survivors to that among a matched comparison cohort to generate new hypotheses. Methods Breast cancer patients sixty-five years or older diagnosed 1990–1994 in six integrated care settings and who survived at least five years were matched with a cohort of women without a history of breast cancer on care setting, age, and calendar ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Younger patients and patients with localised or regional stage breast cancer had higher relative mortality than older patients and patients with distant or unknown spread breast cancer, likely due to modification of the relative rates by the higher baseline mortality rates among older patients and patients with distant and unknown stage breast cancer. Previous investigations demonstrated that five-year breast cancer survivors have a similar frequency of prevalent and incident diseases as women from the general population, in agreement with our study [7,[12][13][14]32]. This similarity is supported by a recent study suggesting that conventional risk factors, such as smoking, diabetes and hypertension are associated with incident cardiovascular conditions in five-year breast cancer survivors rather than a diagnosis of breast cancer as compared with women from the general population [33].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Younger patients and patients with localised or regional stage breast cancer had higher relative mortality than older patients and patients with distant or unknown spread breast cancer, likely due to modification of the relative rates by the higher baseline mortality rates among older patients and patients with distant and unknown stage breast cancer. Previous investigations demonstrated that five-year breast cancer survivors have a similar frequency of prevalent and incident diseases as women from the general population, in agreement with our study [7,[12][13][14]32]. This similarity is supported by a recent study suggesting that conventional risk factors, such as smoking, diabetes and hypertension are associated with incident cardiovascular conditions in five-year breast cancer survivors rather than a diagnosis of breast cancer as compared with women from the general population [33].…”
Section: Discussionsupporting
confidence: 92%
“…Patients with comorbidity potentially receive a modified course of treatment and have poorer survival than otherwise healthy breast cancer patients [4][5][6][9][10][11][12]. Recent studies from the United States documented that older five-year breast cancer survivors have approximately similar incidence of new medical conditions as agematched women from the general population [13][14][15]. Incident diseases were associated with seven-fold increased mortality among women from the general population but only four-fold among the breast cancer survivors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse symptoms and complications, termed late effects , can arise from breast cancer and its treatments long after diagnosis [9]. Research on late effects predominantly focuses on biomedical sequelae [10]; long-lasting changes in other aspects (e.g., psychological, social, vocational, financial, functional) of patients’ lives—a concept we call collateral damage [11, 12] requires study. Characterizing MBC-specific collateral damage is important to better understand and improve the lives of people with MBC, as was the primary goal of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in a long-term survivor cohort and cancer-free controls, there was no difference in newly diagnosed diseases [22] in over 10 years of follow-up. There were even slight shifts to the left for circulatory diseases.…”
Section: Discussionmentioning
confidence: 91%